Intimate enemy : loss and recovery of self under colonialism (Oxford University Press, 1983)
Political, economic, and cultural domination under colonialism has repeatedly been studied during the last hundred years. Breaking with the tradition, Ashis Nandy explores the ways in which colonialism damaged the colonizing societies themselves, and how the likes of Gandhi resisted their rulers in British India by building on the lifestyle, values, and psychology of ordinary Indians and by heeding dissenting voices from the West.